Laparoscopic floppy Nissen fundoplication: evaluation of outcome in 34 patients operated without prior oesophageal pH and manometry - Prasad, Dinesh; Kumar, Abhishek; Modh, Foram; Gehlot, Vishnu; Kothari, Purva (International Surgery Journal, 2020)
Background: Aim of the study was to evaluate prospectively the outcomes of laparoscopic floppy Nissen fundoplication in cohort of patients with typical symptoms of gastroesophageal reflux disease (GERD) and hiatus hernia without pre-operative 24 hours oesophageal pH and manometry study. Methods: Thirty-four patients with typical symptoms of GERD, from March 2009 to November 2019, were studied. The study was limited to patients with positive findings on upper GI endoscopy done by operating surgeon with typical symptoms (heartburn, regurgitation, and dysphagia) of GERD and hiatal hernia. Laparoscopic Nissen’s fundoplication was performed when clinical assessment suggested adequate oesophageal motility and length. Only 1 patient, who had negative endoscopic findings, underwent a 24-hour pH-monitoring before surgery. Outcome measures included assessment of the relief of the primary symptom responsible for surgery in the early postoperative period; the patient’s evaluation of outcome and quality of life after surgery. Result: Laparoscopic Nissen’s fundoplication is an effective long-term treatment for GERD and may be performed in patients with typical symptoms of GERD and hiatus hernia and endoscopic findings suggestive of reflux esophagitis and patient who wants to get rid of life long proton-pump inhibitors (PPI) and antacids medication. Conclusions: Preoperative oesophageal manometry and 24-hour pH monitoring are not mandatory for laparoscopic fundoplication if the patient selection is appropriate but may be required in selected patients with atypical symptoms.